Sustainability competencies within the universities: systematic literature review (Research, Society and Development, 2021)
It’s a well-known fact that universities have the power to change society. For this reason they are considered key actors of sustainable development. Education was highlighted in the 2030 Agenda increasing the number of papers pertaining to universities' role in this pursuit. This paper aims to understand how international research is being developed on the matter of sustainability in universities. For that, our methodology of choice was a bibliometric mapping followed by a systematic revision of published material on the topic. Our source for data was the Scopus platform.Results show us that the studies are mostly being developed from an academic perspective with sustainable competences aiming towards the students who are seen as the future professionals who will be making important decisions. From that we conclude that sustainable management of universities particularly focusing on development sustainable competencies is a research field that hasn’t been fully explored yet even though these institutions are recognized as catalysts for change and understood as having a key role on sustainable development.